Is family relations related to health service utilisation among older immigrants: Evidence from Chinese elderly in the United States. (27th August 2018) - Guo, Man; Sabbagh Steinberg, Nadia; Dong, Xinqi; Tiwari, Agnes
Abstract: The family is the key for survival and success of the 4.6 million older immigrants in the United States. It is also an overlooked context to understand older immigrants' health service utilisation. Most prior studies on this topic either focus on individual or institutional factors that affect how older immigrants use formal health services. Using data from 2011 Population Study of Chinese Elderly in Chicago ( N = 3, 159), this study examined potential linkages between family relationships and health service utilisation among US Chinese elderly. Negative binomial and logistic regressions were carried out to investigate whether health service use of these older immigrants are related to positive family relations, negative family relations, and health‐related communications among family members. The findings showed that positive spousal or family relations were not associated with either physician visits or hospital stays. However, respondents with more negative family relations had more doctor visits (β = 0.065, p < 0.05) and were marginally more likely to use inpatient services (OR = 1.15, CI: 0.88–1.04, p = 0.08). Respondents who talked to their spouse for medical concerns were less likely to use inpatient services (OR = 0.68, CI: 0.46–0.99, p < 0.05). The findings showed that family relations play a role in Chinese older immigrants' health service use. In addition, family conflict seems to be more influential than close family relations in predicting service use. Practitioners need to thoroughly assess family dynamics to fully understand the resources and barriers for health service utilisation among the older immigrant populations.